“I Can’t Control It”: Lila Avilés’s Feature Films as Environmental Mourning - Anzzolin, Kevin (Lagoonscapes)
Climate change has had a profound impact on Mexico. Notably, in 2024, climate scientist Claudia Sheinbaum was elected president. Mexican filmmaker Lila Avilés’s two feature films – La camarista (The Chambermaid, 2018) and Tótem (Totem, 2024) – have garnered significant press attention but little scholarly analysis. Through a detailed examination of Avilés’s portrayal of hygiene and animals, the author argues that the films highlight humanity’s interconnectedness with nature and reflect the failed efforts – through religion, psychology, politics, and other means – to control it. In this sense, Avilés films the ‘anthropological machine’ in the making, and these works should be understood as instances of environmental mourning.